Calvatone (CR). Costa di Sant’Andrea - Area di proprietà provinciale. Un nuovo mosaico dal vicus di Bedriacum (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
The annual archaeological excavations – organized by the University of Milano – at the vicus of Calvatone-Bedriacum has brought to the identification of a great residential building. It is important the recent discovery of a triclinium characterized by a cocciopesto floor. The floor presented a black and white device in tessellating paving, furthermore the central part is adorned with a kantharos  enclosed by peltas (peltae) and birds inside geometrical spaces.
Keywords: Calvatone; Bedriacum; mosaic; kantharos; vicus; triclinium